Individual and combined effects of acute and chronic running loads on injury risk in elite Australian footballers - Murray, N. B.; Gabbett, T. J.; Townshend, A. D.; Hulin, B. T.; McLellan, C. P. (Scandinavian Journal of Medicine & Science in Sports, 2017)
A model that takes into account the current workload, and the workload the athlete has been prepared for, as an acute:chronic workload ratio has been previously used as a novel way to monitor training load and injury risk. Fifty-nine elite Australian football players from one club participated in this 2-year study. Global Positioning System technology was used to provide information on running workloads of players. An injury was defined as any non-contact "time-loss" injury. One-week (acute), along with 4-week (chronic) workloads were calculated for a range of variables. The size of the acute workload in relation to the chronic workload was calculated as an acute:chronic workload ratio. An acute:chronic workload ratio of >2.0 for total distance during the in-season was associated with a 5 to 8-fold greater injury risk in the current [relative risk (RR) = 8.65, P = 0.001] and subsequent week (RR = 5.49, P = 0.016). Players with a high-speed distance acute:chronic workload ratio of >2.0 were 5-11 times more likely to sustain an injury in the current (RR = 11.62, P = 0.006) and subsequent week (RR = 5.10, P = 0.014). These findings demonstrate that sharp increases in running workload increase the likelihood of injury in both the week the workload is performed, and the subsequent week.